Analisis Faktor – Faktor yang Mempengaruhi Kesejahteraan Lanjut Usia di Kecamatan Denpasar Barat (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The increasing number of elderly people in Denpasar City is a direct consequence of the rising life expectancy achieved through improvements in healthcare quality and social conditions. This phenomenon indicates the occurrence of population ageing, which on the one hand reflects the success of development, but on the other hand poses new challenges for the government and society in ensuring the sustainable welfare of the elderly. These challenges encompass economic, social, educational aspects, as well as adequate family support. This study aims to analyze the influence of income, education level, employment status, and family support on the welfare of the elderly in West Denpasar District, which is one of the areas with a relatively significant elderly population. This research employs a quantitative approach with an associative research design to examine the relationships among the variables studied. The sample used in this study consisted of 100 elderly respondents selected based on the research criteria. The results indicate that simultaneously, income, education level, employment status, and family support have a significant effect on the welfare of the elderly in West Denpasar District. Partially, income, education level, and family support have a positive and significant effect on elderly welfare, while employment status does not have a significant effect on the welfare of the elderly in West Denpasar District.